Returnee Executives, Corporate Social Responsibility, and Stock Price Synchronicity - Gao, Di; Zhao, Yuan; Tian, Qinghua (Frontiers in Psychology, 2022)
Executive characteristics have a significant impact on corporate decision-making, corporate sustainable behavior and stock market performance, which may influence the corporations’ sustainable development in the long-run. The role of returnee talents in the corporate sustainable development has received extensive academic attention. Using data of Chinese A-share listed companies over the period of 2008 - 2018, we find that there is a negative relationship between executives’ foreign experience and stock price synchronicity. We also prove that CSR has a significant mediating effect on the relationship between returnee executives and stock price synchronicity. The returnee executives tend to pursue long-term sustainable activities and improve CSR engagement quality, thereby reducing stock price synchronicity. Our extended analysis reveals that the benefit of returnee executives is more pronounced for non-SOEs and for firms located in regions with a low degree of marketization. This study has some implications for the Chinese firms in relation to their CSR information disclosure behaviour, and it gives suggestions to strengthen capital market efficiency for the sustainable development of corporations.